Why we shouldn't let sleeping dogmas lie: a partial reply to Craig - Mooi, Randall D.; Gill, Anthony C. (Zootaxa, 2011)
Now, when I have spoken on these matters in the past, it has sounded to some as if I had taken upon myself the task of denigrating paleontology and individual paleontologists. That is not so. I am concerned with what I find is a real problem.—Nelson, 1969 in Williams and Ebach, 2004: 711